O‘ZBEK XALQ MAQOLLARIDA ANTITEZANING IFODALANISHI - Eshmanova, B.X. (SCIENCE and SOCIETY, 2023)
The article describes the differential semantic proverbs, which reveal the features of lexical-semantic contradictions in them through several proverbs.